渐开线直齿锥齿轮等距修形正交优化设计 - 张方友; 崔焕勇 (Jixie Chuandong, 2013)
For the phenomenon of meshing interference,impact and end contact of spur bevel gear in working,the idea of orthogonal design for isometric modification is put forward,the principle of isometric modification and its manufacturing process is introduced.In order to optimize the effect of modification,the amount of isometric modification,modification height and the modification area of these three factors most affect the effect on modification are identified,three levels of each factor are selected for orthogonal experimental design,and then three-dimensional solid models of standard gears and modification gears are established by SolidWorks,based on gear dynamic FEA simulation analysis with ANSYS/LS-DYNA,the various factors affect the degree of importance on the effect of isometric modification is identified,and then the optimal isometric modification parameters are obtained.Through the simulation analysis,the results indicate that optimal isometric modification not only reduce meshing interference,impact and v